Mapping Indonesian University Students’ Attitudes Toward Statistics Using the Indonesian SATS-36 - Laila Hayati; Sri Subarinah; Arjudin; Sudi Prayitno; Amniatin Naqiyah (Universitas Pendidikan Mandalika, 2026)
As statistics becomes increasingly important in higher education, understanding students’ attitudes toward statistics is essential for improving statistics instruction and learning engagement. This cross-sectional descriptive-correlational study presents a descriptive attitudinal profiling of Indonesian university students’ attitudes toward statistics using the validated Indonesian version of the Survey of Attitudes Toward Statistics-36. Data were collected from 310 students across several Indonesian universities, representing mathematics education, statistics, and other academic programs. Guided by five attitude dimensions (Affect, Cognitive Competence, Value, Difficulty, and Interest/Effort), the findings reveal a distinctive attitudinal pattern. Students reported low affect toward statistics while showing relatively high interest and effort, suggesting a possible affective-motivational divergence. They also recognized the value of statistics while maintaining negative emotional responses, reflecting a cognitive-affective gap. Perceptions of difficulty were generally moderate across academic programs, while motivation and perceived value tended to decline across semester stages. Among the five dimensions, perceived value emerged as an important leverage point for strengthening students’ engagement with statistics, as indicated by its positive association with interest/effort (r = 0.425). These findings suggest that Indonesian students’ attitudinal patterns toward statistics may not be fully captured by conventional affective-behavioral assumptions. Statistics instruction should strengthen the perceived relevance of statistics while directly addressing students’ emotional resistance and learning difficulties.